The Essence of Evidence from Witness Testimony in Canonical Marriage Processes - Janowski, Przemysław (Prawo Kanoniczne, 2026)
The problem addressed: The main impetus for addressing the issue raised in the article was the desire to present the nature of witness testimony as evidence in the context of matrimonial cases governed by ecclesiastical law. Literature on witnesses in canon law is extensive. However, there is a scarsity of studies that attempts to compare the value of witness evidence simultaneously in various matrimonial proceedings. The aim of the research conducted: Presentation of the nature of witness testimony as evidence in matrimonial processes regulated by church authority. Methods: A theoretical-legal method was used. The study presents the nature of the institution of witness in matrimonial processes regulated by church authority. The results of the research: The nature of witness testimony as evidence is related to the type of matrimonial process. The conclusions drawn from the research: In matrimonial processes, the nature of witness testimony as evidence is related to factors that determine the procedural situation, such as the party who calls the witness, the procedural mode and the title of the legal claim (particularly in cases concerning the declaration of nullity of marriage and separation). Witness testimony as evidence is not necessary in all matrimonial processes.